Oral Complications in Cancer Patients–Medication-Related Osteonecrosis of the Jaw (MRONJ) - Migliorati, Cesar Augusto (Frontiers in Oral Health, 2022)
Medication-Related Osteonecrosis of the Jaw (MRONJ) was first reported in 2003. Despite the progress in the understanding of this oral complication in cancer patients for the past 18 years, there is still discussion about the best way to define MRONJ, prevent the complication, how to diagnose, and the options of treatment available. The initial reports associated MRONJ to bisphosphonates and denosumab, medications that work as bone-modifying agents. Later, other agents such as the antiangiogenics, have also been reported to cause the oral complication, either alone or in combination with antiresorptives. Initially, these medications were prescribed to patients with osteoporosis and cancers patients with bone metastasis. Today, because of the effect of the medications in the bone remodeling system, patients with several other diseases such as giant cell tumors, rheumatoid arthritis, Paget’s disease of bone, fibrous dysplasia, osteogenesis imperfecta, are managed with these medications, significantly increasing the population of individuals at risk for developing MRONJ. This mini review focused on the cancer patient. It updates the dental clinician on the recent scientific literature about MRONJ and provides information on how to diagnose and manage patients being treated with these medications, suggests protocols to prevent the development of MRONJ, and present ways to manage those patients who develop the oral complication.